Investigation of the Al-adhesive transfer mechanism on Ti6Al4V blade tips under high-speed rubbing in an aero-turbine engine. (December 2022) - Wu, Bi; Gao, Siyang; Zhang, Ronglu; Xue, Weihai; Li, Shu; Duan, Deli
Highlights: The Al-adhesive transfer phenomena from the Al-hBN seal coating to the Ti6Al4V blade tip in an aero-turbine engine was reproduced using the high-speed-rubbing test rig. A gradient interface reaction interlayer between the Al-adhesive transfer layer and the Ti6Al4V blade tip was observed only under the higher sliding speed (300 m/s). The tribology interface reaction and thermal stress distribution model of the Al-adhesive Ti6Al4V blade tip is proposed to reveal the Al-adhesive mechanism during the high-speed-rubbing process. Abstract: The Al-hBN seal coating invariably transfers to the tip of the Ti6Al4V blade under high-speed rubbing, resulting in the deterioration of the power and the reliability of the developed aero-engine. The Al-adhesion phenomenon was reproduced using a high-speed rubbing test rig at 90 m/s and 300 m/s. The results showed that the coverage rate and thickness of the Al-adhesive transfer layer were higher at 300 m/s than at 90 m/s, which could be attributed to the Ti-Al interface reaction. The interface microstructure and the thermal stress distribution model were proposed to reveal the mechanism of the Al-adhesive transfer under conditions of high-speed rubbing. A gradient interface reaction interlayer composed of TiAl3 and γ-TiAl between the Al-adhesive transfer layer and the Ti6Al4V blade tip was observed only at 300 m/s. This interface reaction interlayer could release the thermal stress and enhance the adhesion between the Al-adhesive transfer layer and the Ti6Al4V blade tip.